The Evolutionary Dynamics of Battery Technology: A Knowledge-Based Assessment from Article Publications - Ferrer, Eva Sofia Gonçalves (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics